PROSPECT IN TREATMENT OF JUVENILE RHEUMATOID ARTHRITIS WITH ADALIMUMAB - E.I. Alexeeva; T.М. Bzarova; S.I. Valieva; R.V. Denisova ("Paediatrician" Publishers LLC, 2008)
This review is dedicated to treatment of rheumatoid diseases in adults and children with one of TNF blockers adalimumab. The data from single, open9labeled, and multicenter double blinded placebo controlled studies of effectiveness and safety of adalimumab is presented. Analysis of many published information showed high activity and safety of adalimumab for treatment of rheumatoid arthritis, ankylosing spondylitis, rheumatoid uveitis in adults and children.Key words: children, rheumatoid arthritis, juvenile rheumatoid arthritis, uveitis, treatment, adalimumab.